(untitled) (Raparin Journal of Humanities (RJH), 2024)
This research aims to shed light on the role of media spokesmen of official institutions in the Kurdistan Region during critical periods. The research consists of a descriptive approach while it has used a survey method including a research instrument in the form of a questionnaire. The latter was designed via the survey administration software Google Forms whereas its link was distributed in a group chat containing journalists from the Kurdistan Region. The questionnaire reached 70 responses. The most important findings in the current study are related to the research samples claiming that the news and information conveyed by the spokesmen from official institutions were ineffective. In addition, the research findings also display that the spokesmen have played a weak role in managing critical periods in Kurdistan Region.